Editorial for the Special Issue on Parallel and Concurrent Functional Programming - Keller, Gabriele; Henglein, Fritz (Journal of functional programming, 2018)
Functional languages are uniquely suited to providing programmers with a programming model for parallel and concurrent computing. This is reflected in the wide range of work that is currently underway, both on parallel and concurrent functional languages, as well as on bringing functional language features to other programming languages. This has resulted in a rapidly growing number of practical applications. The Journal of Functional Programming decided to dedicate a special issue to this field to showcase the state of the art in how functional languages and functional concepts currently assist programmers with the task of managing the challenges of creating parallel and concurrent systems.